HOW DID JOSEPH BECOME THE SHEPHERD OF HIS BROTHERS? - Nguyen, Chi (Science et Esprit, 2022)
Through a narrative reading of Genesis 37-50, we will follow Joseph’s journey in order to show how he became the shepherd of his brothers. At the beginning of the story, Joseph is seen as someone who “was shepherding his brothers,” an indication that anticipates the essential traits of his mission. In order to accomplish his mission, Joseph first needed to go beyond the boundaries of the sheepfold for which he was responsible. Indeed, being victim of his own flock, he took some detours (from being the favored son sent by the father to being a slave and a prisoner) before becoming the shepherd of his brothers in a new way and in a new context. His journey was extraordinary because he went to the peripheries in order to become the center, not only of his own family but also of Egypt. The purpose of our paper is to show how Joseph, by handling violence with tact, can be a model for those who take care of others in a challenging situation.